2009
DOI: 10.1038/nrrheum.2009.229
|View full text |Cite
|
Sign up to set email alerts
|

The role of microparticles in the pathogenesis of rheumatic diseases

Abstract: Microparticles (MPs) are small membrane-bound vesicles that are emerging as important elements in the pathogenesis of rheumatic diseases owing to their pleiotropic effects on thrombosis, vascular reactivity, angiogenesis and inflammation. Released from cells during activation and apoptosis, MPs carry proteins, lipids and nucleic acids, and serve as platforms for enzymatic processes in thrombosis. Furthermore, MPs can transfer cytokines, receptors, RNA and DNA to modulate the properties of target cells. As MPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
212
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(224 citation statements)
references
References 92 publications
4
212
0
8
Order By: Relevance
“…Consequently, the proportion of circulating cell-derived MPs with surface-bound IgG was significantly increased in the SLE group (median [5th-95th percentile] 3.5% [0. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].3%] in the SLE patient group versus 0.4% [0.02-4.3%] in the healthy control group; P Ͻ 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the proportion of circulating cell-derived MPs with surface-bound IgG was significantly increased in the SLE group (median [5th-95th percentile] 3.5% [0. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].3%] in the SLE patient group versus 0.4% [0.02-4.3%] in the healthy control group; P Ͻ 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Circulating cell-derived MPs are heterogeneous submicrometer-sized vesicles that are shed from the surface of cells, constitutively or during activation or apoptosis (10,11). Apoptotic MPs formed in vitro contain nuclear autoantigens that are accessible to autoantibodies (6,12,13).…”
mentioning
confidence: 99%
“…Microparticles (also called extracellular vesicles) are submicrometer‐sized membrane vesicles (0.05–1 μm diameter) that are actively shed from cells in response to activation, injury, and apoptosis 15, 16. A number of recent studies have shown that diseases of the vasculature and kidneys, including CKD, are associated with increased numbers of circulating endothelial microparticles 17, 18, 19, 20, 21, 22.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their abundance, platelet-derived MPs (PMPs) received the highest attention during the past few years. Elevated PMP counts are characteristic for nearly all autoimmune disorders [4,5], and also for several cardiovascular and metabolic diseases [1]. EVs not only contain proteins but also RNA molecules [1].…”
mentioning
confidence: 99%